Pengaruh Job Insecurity, Job Stress dan Job Satisfaction Terhadap Turnover Intention Karyawan PT. Trans Ocean Services Indonesia - Indar, Irma Ariani Nur; Rizqi, Maulidyah Amalina (Jurnal Mahasiswa Manajemen, 2024)
Background - PT. Trans Ocean Services Indonesia, a company engaged in transportation management services (JPT) or Freight Forwarding. In 2022, there were employees who left the company every month because of the employee's own wishes and the company did not extend the employee's contract Objective - This study aims to test job insecurity, job stress and job satisfaction on turnover intention at PT. Trans Ocean Services Indonesia. Design / Methodology / Approach - The population used in this study were all permanent employees working at PT. Trans Ocean Services Indonesia, totaling 61 people with a saturated sampling technique, namely a sampling technique where all members of the population were sampled. The data source in this study is primary data, namely the results of distributing questionnaires to respondents, namely employees of PT. Trans Ocean Services Indonesia. The type of data used is subjective data in the form of written responses as questionnaire responses. The analysis model used in this study is a multiple linear regression analysis model. Findings - Job insecurity has been shown to have a positive and significant effect on turnover intention. job stress has been shown to have a positive and significant effect on turnover intention. Job satisfaction has been shown to have a positive and significant effect on turnover intention. Research Implications – The level of job insecurity given by the company to employees can be seen from the meaning of the job for the individual, the level of threat felt by employees regarding aspects of the job, the level of threat that is likely to occur and affect the overall work of the individual, the helplessness of the individual and the level of threat to the job in the following year. The level of job stress given by the company to employees can be seen from the demands of the task, the demands of the role, the demands of interpersonal relationships, the organizational structure and the leadership of the organization providing a management style to the organization. The level of job satisfaction given by the company to employees can be seen from the work, wages, promotions, supervisors and co-workers. Research Limitations – The research will provide valid results for the company that is the object of the research